2011
DOI: 10.1002/ajmg.a.34146
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in the range of joint motion in seven patients with mucopolysaccharidosis type II during experimental gene expression‐targeted isoflavone therapy (GET IT)

Abstract: Mucopolysaccharidosis type II (MPS II, Hunter disease) is an X chromosome-linked inherited metabolic disease caused by mutations resulting in deficiency of activity of iduronate-2-sulfatase (IDS) and accumulation of undegraded glycosaminoglycans (GAGs), heparan sulfate, and dermatan sulfate. Previous experiments with cell cultures and studies on animal model of MPS II suggested that gene expression-targeted isoflavone therapy (GET IT), based on genistein-mediated reduction of efficiency of GAG synthesis, might… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 27 publications
1
33
0
1
Order By: Relevance
“…Since it slows down the production of glycosphingolipids, it should be effective in reducing storage of these compounds. Although positive effects of such treatment in clinical trials were reported (Elstein et al 2004;Pastores et al 2005), its efficacy in Gaucher disease has recently been questioned (Tylki-Szymanska et al 2011;Machaczka et al 2012).…”
Section: Substrate Reduction Therapies (Srps) For Mpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since it slows down the production of glycosphingolipids, it should be effective in reducing storage of these compounds. Although positive effects of such treatment in clinical trials were reported (Elstein et al 2004;Pastores et al 2005), its efficacy in Gaucher disease has recently been questioned (Tylki-Szymanska et al 2011;Machaczka et al 2012).…”
Section: Substrate Reduction Therapies (Srps) For Mpsmentioning
confidence: 99%
“…Therefore, it was suspected that higher doses of genistein might be considerably more efficacious (Wegrzyn 2012), especially since the most positive effects were reported in mice at genistein dose of 160 mg/kg/ day (Malinowska et al 2010), which is more than 10 times higher than the highest dose used to date in published human studies (Malinova et al 2012). On the other hand, recent clinical report indicated that not only MPS III but also MPS II patients may potentially benefit from GET IT as a special kind of SRT (Marucha et al 2011). An important finding is a lack of adverse effects in all the studies on SRT for MPS reported to date and cited above.…”
Section: Efficacy Of Srt In In Vitro Studies Experiments With Animalmentioning
confidence: 99%
“…In all studies on experimental GET IT for MPS patients published to date, a genistein-rich isoflavone extract was used with the genistein dose of 5 mg/kg/day Delgadillo et al 2011;Marucha et al 2011). However, authors of the most recent studies suggested that an increase in the genistein dose might result in higher efficacy of GET IT (Delgadillo et al 2011;Piotrowska et al 2011).…”
Section: Introductionmentioning
confidence: 97%
“…Then, a 2-year follow-up study was performed, indicating that at this particular dose of genistein, after the initial improvement, the patients' state stabilized (in some patients) or slowly deteriorated (in other patients) . Another recent study showed that GET IT may be useful in treatment of patients suffering from MPS II (Hunter disease), another type of MPS in which a large fraction of patients suffers from deterioration of brain functions (Marucha et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Although genistein appears to be well tolerated in high doses, adverse effects, which are associated with its potential antiproliferative and estrogenic actions, have been reported and may include hepatotoxicity and hormonal disbalance (Kim et al 2013;Singh et al 2014). The only study on the effects of genistein on MPSrelated bone disease showed increased range of joint motion in genistein-treated MPS II patients, suggesting that genistein at least reaches the surrounding connective and muscle tissue of the joints (Marucha et al 2011). Because genistein can reach the bone tissue (Coldham and Sauer 2000), we fed MPS I mice a high-dose genistein diet to evaluate its potential for the treatment of MPS I-related bone disease.…”
Section: Introductionmentioning
confidence: 99%